О возрастных особенностях роста и развития некоторых видов деревянистых лиан при интродукции в Донбасс - Костырко, Д.Р. (Промышленная ботаника, 2002)
Growth and development peculiarities of 22 arboreous lianes species from the Donetsk botanical gardens collection have been studied. Four age periods of development can be traced differing by their duration. According to the data of 35 years introduction trial, arboreous lianes when grown in Donbass are characterized by an insufficient practical longevity. The revealed growth and development age peculiarities of the studied species on one hand, have a theoretic significance for substantiation of introduced lianes life span in Donbass and can be regarded as indication of their survival and adaptive capacity and on the other hand, they have a practical importance for determining the assortment for greenery planting in every concrete plot, and in the whole for prognosticating arboreous lianes of introduction success in the region.